Internal Colonialism, Alien Rule, and Famine in Ireland and Ukraine - Hechter, Michael (East/West, 2021)
The Irish famine of the mid nineteenth century and the Ukrainian famine of the twentieth century have been the subject of large and quite contentious literatures. Whereas many popular explanations of the Irish famine attribute it to the English government’s infatuation with laissez-faire economic doctrines, by contrast the Ukrainian famine has often been ascribed to Stalin’s resentment of Ukraine’s resistance to the Soviet revolution. This essay suggests that despite their many differences, during these years both Ireland and Ukraine can be considered to have been internal colonies of their respective empires. The key implication of this conception is that these appalling famines arose from a common underlying cause: namely, the inferior political status of these regions relative to that of the core regions of these states. One of the defining characteristics of internal colonies is that they often suffer from alien rule. Alien rulers are typically indifferent to the welfare of the residents of the culturally distinctive regions within their borders. Due to this indifference, both the British and Soviet central rulers cast a blind eye to the fate of the Irish and Ukrainian peasants.